RANCANG BANGUN SISTEM INFORMASI PENGAJUAN KREDIT BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER (STUDI KASUS : BPR TALA) - Muhammad Sihrowardi; Abdullah Ardi (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2021)
Currently this technology has had a major influence on the way of life and lifestyle so that it has spread to all domains, including credit applications that have made major changes to digital forms. Applications for credit at the Tanah Laut people's credit bank are still done manually starting from the credit application process, processing data and files, to preparing reports. This causes the credit application process to be ineffective and takes a long time, so that it can negatively affect customer satisfaction. This credit application system was developed on a web basis using a codeigniter framework, with the waterfall development method. This system can apply for credit online, helps make it easier to make decisions in determining the receipt of credit applications, helps in making monthly reports.